Vapor-Liquid Equilibrium Measurements of Polymeric Solutions – A Review - Ianatul Khoiroh (Universitas Lambung Mangkurat, 2020)
The nature of the molecule of the substance depends heavily on its physico-chemical properties. An accurate and reliable measurement of physical properties is therefore, essentially needed as a framework to gain a comprehensive understanding of the molecular behavior. Of these properties, saturated pressure is one of the most important thermophysical properties in the design of products, equipment, and processes in various chemical industries. In this review, various techniques that have been utilized in measuring the vapor-liquid equilibrium (VLE) for polymeric solutions are discussed.Keywords: VLE, polymer, measurements, pressure.